PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MIND MAPPING TERHADAP KEMANDIRIAN BELAJAR SISWA PADA PEMBELAJARAN IPS - Agus Ridwanulloh (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2024)
Independent learning at school has not shown positive results. Several surveys show that many students still do not have an independent attitude. The causal factor is that learning is still teacher-oriented. Teachers are still the only source of knowledge which causes student dependency, thus affecting independence. This research aims to (1) analyze the effectiveness of the problem based learning model assisted by mind mapping in increasing independence, and (2) analyze the increase in independence in the problem based learning model assisted by mind mapping. This research was carried out at SDN Randegan Kulon I and SDN Randegan Kulon II, Majalengka Regency. This type of research uses quasi-experiment. The method used is a quantitative method. The population of all class V at SDN Randegan Kulon I and II in 2021/2022 is 65 students. The research subjects were 32 experimental classes at SDN Randegan Kulon I and 33 control classes at SDN Randegan Kulon II. Sampling used nonprobability sampling with saturated sampling techniques. Research data was obtained from pretest-posttest, questionnaires, observation and documentation. Data analysis uses normality test, homogeneity test, sample t-test, gain test, and effective contribution. The research results show: (1) The problem based learning model assisted by mind mapping is effective in increasing student independence: (a) classical completeness score is 93.75%, (b) average score is 83, (b) and gain score is 0.49 by category currently. (2) The problem based learning model assisted by mind mapping is effective in increasing learning independence: (a) classical completeness value is 93.75%, (b) average value is 81, (c) and gain value is 0.50 in the medium category. (3) There is a significant difference in students' learning independence after being given treatment using the problem based learning model assisted by mind mapping with an average pretest score of 61.34 and posttest 80.78, an increase of 19.44.